A noção de trabalho no ensino médio noturno: um estudo dos discursos dos jovens e dos documentos das políticas educacionais - Perin, Adriana Regina Menegatti (2019)
Work is constitutive of the human being. At the same time, in the area of education, it is a strong tensioner for understanding world production. In this complex, the school also has the function of preparing the subject to live and interact with this world, which meets the (social) demand of youths studying at Night High School (EMN). Against this background, the question to which we pursue an answer in this research is: why does the notion of work apprehend specificities in EMN? This problem aims to understand specificities of the notion of work in the EMN, to reflect on its principles in the field of education. The methodology used for this investigation involves: empirical research through the study of the discourses of young people studying at the EMN in Chapecó-SC, documentary research with the study of the discourses in the national and state educational policy documents, and bibliographic research, based on especially researchers in the field of education. We rely on the Discursive Textual Analysis (ATD) proposed by Moraes and Galliazi (2006), for the study of empirical and documentary data, to sculpt preparatory and comprehensive confluences. We organized the dissertation, analyzing the discourses about the notion of work from the words of the youths of the night high school in the city of Chapecó-SC and from the educational policy documents, and we channeled to the discursive confluences, which express coexistent multiplicities. We infer that in the empirical and documentary discourses the relationship between work and education in the EMN is predominantly related to the notion of employment. In general, they disregard teaching and learning relationships, which are in line with emancipatory knowledge, and which could be assumed by understanding work as an educational principle, since this articulation is one of the striking specificities of EMN courses.